Wattpad: A Strategy for Improving the First-Graders' Descriptive Text Comprehension - Eka Mayasari (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research was motivated by the lack of students' interest in English lessons, especially in writing descriptive texts. The purpose of this research was to determine the extent to which the use of the Wattpad application could influence students' ability to write descriptive texts. This research was conducted at MA Miftahul Ulum Tanjungpinang in the first-grades students in the second semester of the academic year 2022-2023. This research was a quantitative study using an experimental method. The sample of this research was 50 students. The research method used was a true experiment with a post-test only control design. The result of the research, there is a significant difference between the writing scores of the experimental class and the control class where the post-test scores of the experimental class are higher. It can be seen that the mean value of the control class is 62,12 while the experimental class is 75,64. Thus, it can be concluded that there is a significant effect of using the Wattpad application on the ability of the first-grade students at MA Miftahul Ulum Tanjungpinang to write descriptive texts. based on student’s feedback using Wattpad application, the results show a strong positive trend across all questions related to Wattpad. Respondents tend to strongly support the statements provided. Mostly showed a positive “Strongly Agree” toward each statement, with only a few being neutral, disagreeing, or strongly disagreeing suggesting that the students had a favorable perception to the Implementation of the Duolingo application on the writing skill of the eleventh-grade students at MA Miftahul Ulum Tanjungpinang.